Cytotoxic Activity of Ethyl Acetate Extract from Voacanga foetida (Bl.) Rolfe Leaves Against T47D Breast Cancer Cells - Adriani Susanty; Mira Febrina; Dian Sanita Putri; Ihsan Ikhtiarudin; Fatma Sri Wahyuni; Dachriyanus Dachriyanus (Borneo Journal of Pharmacy, 2023)
The cytotoxicity of ethyl acetate extract from Tampa badak (Voacanga foetida (Bl.) Rolfe) leaves against Artemia salina leach larvae was determined using the brine shrimp lethality test (BSLT) method and was evaluated against T47D breast cancer cells using MTT assay method. The result of BSLT showed a consistent result with MTT assay, which is the result obtained that ethyl acetate extract is very toxic against A. salina Leach larvae with LC50 value of 8.61 µg/mL and very cytotoxic against T47D breast cancer cells with IC50 values of 0.87; 0.66; and 0.95 µg/mL at the 24, 48 and 72 hours of incubation times, respectively. The MTT assay data were analyzed using a two-way ANOVA statistical method to see the effect of the dependent variable (concentration and time) on the independent variable (% viability). Based on the statistical test result, there is a difference in % viability between concentrations of 0.1; 1; and 10 µg/mL (p <0.05), but the length of incubation does not affect % viability (p >0.05).